Proceedings of the 4th Information Interaction in Context Symposium 2012
DOI: 10.1145/2362724.2362779
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking radio broadcasts

Abstract: This poster reports the preliminary results of a user study uncovering the information seeking behaviour of humanities scholars dedicated to radio research. The study is part of an interdisciplinary research project on radio culture and auditory resources. The purpose of the study is to inform the design of information architecture and interaction design of a research infrastructure that will enable future radio and audio based research. Results from a questionnaire survey on humanities scholars' research inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Content segmentation Studies for both TV and radio content have shown that users tend to consume program segments rather than entire programs when accessing content on demand. For example, the authors of [37] report that 48% of the respondents in their study found it important to easily locate a part (or section) of a radio program. This means that content needs to be structured into semantically meaningful temporal units.…”
Section: Content Enrichmentmentioning
confidence: 99%
“…Content segmentation Studies for both TV and radio content have shown that users tend to consume program segments rather than entire programs when accessing content on demand. For example, the authors of [37] report that 48% of the respondents in their study found it important to easily locate a part (or section) of a radio program. This means that content needs to be structured into semantically meaningful temporal units.…”
Section: Content Enrichmentmentioning
confidence: 99%
“…Taheri-Panah and MacFarlane [2004] examine music-seeking behavior of users using questionnaires and interviews. Skov and Lykke [2012] study user needs in sound retrieval by means of user studies and surveys. Although sparse, this initial work provides a basis for expanding intent typologies beyond image and video search.…”
Section: Expanding and Consolidating Conceptual Models Of User Intentmentioning
confidence: 99%